Suicide assessment and feasible evidence-based treatments for adolescents living with HIV in Malawi: Protocol for a pilot randomized controlled trial - Melissa A. Stockton; Katherine Waddell; Steven M. Mphonda; Nivedita L. Bhushan; James January; Charles Masulani; Gregory Brown; Michael M. Udedi; Brian W. Pence; Jonathan Chiwanda; Bradley N. Gaynes; Kazione Kulisewa (PLoS ONE, 2025)
Background This pilot trial will investigate the feasibility, acceptability, fidelity, and preliminary efficacy of a combined youth-friendly suicide prevention and problem-solving intervention in reducing suicidal ideation and behaviors in adolescents living with HIV (ALWH) in Malawi. Methods ALWH (N = 60) aged 13–19 who reported suicidal ideation and behaviors will be recruited from 5 health clinics. Participants will be randomized 1:1 either to the Safety Planning and Friendship Bench (SP + FB) (n = 30) or to augmented usual care (n = 30) and followed for 6 months. SP + FB includes 6 individual counseling sessions and 6 bi-monthly peer support group sessions delivered by psychological counselors. Feasibility, acceptability, fidelity, and preliminary efficacy will be assessed at 6-weeks and 3- and 6-month study visits and compared across the 2 study arms. Discussion The results of this study will provide insights into the feasibility, acceptability, fidelity, and preliminary efficacy of the combined SP + FB for reducing chronic and acute suicidality in ALWH compared to standard of care. This pilot study will lay the groundwork to test the SP + FB in a large-scale cluster randomized controlled trial to improve suicide prevention resources and interventions for ALWH in Malawi. The findings of the study will add to a critical body of research aiming to implement feasible, acceptable, and effective suicide prevention interventions as part of adolescent HIV care in low-resource settings. Trial registeration ClinicalTrials.gov: NCT06770101